Role of intestinal epithelial cells in immune effects mediated by gram-positive probiotic bacteria: Involvement of toll-like receptors - Vinderola, Celso Gabriel (2005)
The mechanisms by which probiotic bacteria exert their effects on the immune system are not completely understood, but the epithelium may be a crucial player in the orchestration of the effects induced. In a previous work, we observed that some orally administered strains of lactic acid bacteria (LAB) increased the number of immunoglobulin A (IgA)-producing cells in the small intestine without a concomitant increase in the CD4+ T-cell population, indicating that some LAB strains induce clonal expansion only of B cells triggered to produce IgA. The present work aimed to study the cytokines induced by the interaction of probiotic LAB with murine intestinal epithelial cells (IEC) in healthy animals. We focused our investigation mainly on the secretion of interleukin 6 (IL-6) necessary for the clonal expansion of B cells previously observed with probiotic bacteria. The role of Toll-like receptors (TLRs) in such interaction was also addressed. The cytokines released by primary cultures of IEC in animals fed with Lactobacillus casei CRL 431 or Lactobacillus helveticus R389 were determined. Cytokines were also determined in the supernatants of primary cultures of IEC of unfed animals challenged with different concentrations of viable or nonviable lactobacilli and Escherichia coli, previously blocked or not with anti-TLR2 and anti-TLR4. We concluded that the small intestine is the place where a major distinction would occur between probiotic LAB and pathogens. This distinction comprises the type of cytokines released and the magnitude of the response, cutting across the line that separates IL-6 necessary for B-cell differentiation, which was the case with probiotic lactobacilli, from inflammatory levels of IL-6 for pathogens.